A MS-Excel user friendly tool for the calculation of effective section area for class 4 slender steel section - Yap, Lester Yi Xian (2015)
Cross sections of steel members come in different shapes and sizes. Under different loading cases such as pure compression, pure bending, or a combination of both, the type of stresses exerted on different parts of the cross section varies. A Class 4 element under compression buckles locally before yield strength can be attained, with the stresses exerted being redistributed. Therefore, the resistance of such an element is not fully mobilised and the entire gross cross section area is not fully effective. In project ST34AB, effective area calculations were carried out via the effective width method and a design tool was created to mechanize the process so as to effectively reduce the time spent on the tedious iterative procedure. This design tool incorporates the calculations for two types of cross sections, namely the Roman II section and the Isection with an extra plate. The following report will provide in depth explanations about the principles and calculation steps incorporated in the design tool. For clarity and understanding, the methods and equations adopted for the iterative procedure will be analysed in sequential order. A chapter will be dedicated to Visual Basic for Applications, covering the basic programming techniques and favourable practices for effective user handling, understanding and management of the program.